Systematization of the experience of a collective vocational guidance session through the support of ChatGPT with eleventh-year students of the Colegio Científico Costarricense, Puntarenas Campus (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To systematize the experience of a collective vocational guidance session, supported by the use of ChatGPT, to clear up vocational doubts at the Colegio Científico de Puntarenas, to analyze its uses in the reflection and vocational decision-making of students and to extract learning, good practices and recommendations for future implementations in vocational guidance processes. Methodology: The article is based on Oscar Jara's (2018) experience systematization model, which starts from living the experience, making a systematization plan, and recovering the experienced process to reflect and provide conclusions and recommendations of the lessons learned, from a qualitative perspective. Data were collected from seven students during a 45-minute group guidance session in the first semester of 2024. Results: The ChatGPT artificial intelligence tool was used to support this group career guidance session. This allowed students in their final year of scientific secondary school to explore personal career interests, universities and scholarships, working conditions and professional opportunities, as well as academic and educational information. This information was provided quickly and concisely by the AI, along with the support of a guidance professional mediating the process. Conclusions: ChatGPT facilitates career exploration but requires the support of guidance professionals for a critical and contextualized analysis.
Keywords: career guidance; career choice; artificial intelligence; educational technology; vocational interests